2012
DOI: 10.1038/cmi.2012.32
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal enterotoxin B-derived haptens promote sensitization

Abstract: T helper 2 (Th2) polarization is a major pathological feature in allergic diseases; its etiology is not fully understood. This study aims to elucidate the adjuvant effect of the microbial product-derived small peptides in the initiation of antigen-specific Th2 polarization. In this study, a clinical survey of patients with chronic rhinosinusitis (CRS) and food allergy (FA) was carried out. The Staphylococcal enterotoxin B (SEB)-derived small peptides (Ssps) were examined in the human stool extracts. The format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The present data have expanded the previous findings by showing that SEB induced the expression of Foxp3 or STAT6 in DCs, depending on the concentrations of SEB in the micro‐environment. Our previous work also indicates that the components of SEB serve as a hapten or induce TIM4 expression to promote the development of intestinal allergy.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The present data have expanded the previous findings by showing that SEB induced the expression of Foxp3 or STAT6 in DCs, depending on the concentrations of SEB in the micro‐environment. Our previous work also indicates that the components of SEB serve as a hapten or induce TIM4 expression to promote the development of intestinal allergy.…”
Section: Discussionmentioning
confidence: 87%
“…Staphylococcal enterotoxin B is one of the enterotoxins of S. aureus . S. aureus is a common bacterium distributing extensively on the surface of the body as well as in the airway and the digestive tract . In healthy conditions, the epithelial barrier prevents the products of S. aureus , such as SEB, from being absorbed.…”
Section: Discussionmentioning
confidence: 99%
“…14 We have also found that SEB is decomposed into small peptides in the digestive tracts of patients with food allergies, and then the SEB peptides act as haptens, facilitating the development of food allergies. 15 These studies suggest that the use of SEB as an adjuvant may evoke a severe allergic reaction. To avoid a possible adverse reaction and maintain the immune system to ensure the efficacy of the immunotherapy, we reduced the dose of SEB from 10 mg/mouse in the food allergy study 14 to 2 mg/ mouse in the present study.…”
Section: Discussionmentioning
confidence: 98%
“…Our data indicate that the over expression of Alix also has the inhibitory effect on SEB-induced epithelial barrier dysfunction. Previous studies suggest that SEB facilitates the development of intestinal allergy via modulating dendritic cell properties or act as an adjuvant [ 4 , 20 ]. The present data provide novel information that SEB also compromises the transcellular antigen transport in the epithelial barrier.…”
Section: Discussionmentioning
confidence: 99%